2020
DOI: 10.1002/arp.1803
|View full text |Cite
|
Sign up to set email alerts
|

Joint interpretation of electrical and seismic data aimed at modelling the foundation soils of the Maredolce monumental complex in Palermo (Italy)

Abstract: The monumental complex of Maredolce (Palermo) includes an Arab‐Norman castle that stands on the banks of an artificial lake carved out of the calcarenitic rock that rests on impermeable clays. The lake was originally filled with water, thanks to the channelling of a spring. Over time, the lowering of the water table and the high hydraulic permeability of the calcarenites have caused the lake to dry up. A project to renovate the monumental complex has recently been launched. It also provides the study of a poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To this end, it was beneficial to consider the obtained 3D electrical resistivity models and the results of refraction seismic profiles. However, for a more detailed characterization of the vp and vs. values of lithotypes and the correlation with other observed geophysical parameters, a joint survey Seismic Refraction Tomography (SRT), Electrical Resistivity Tomography (ERT), and Induced Polarization Tomography (IPT) were carried out in coincident position [13]. Furthermore, a Transient Electromagnetic (TEM) survey was performed nearby.…”
Section: New Geophysical Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, it was beneficial to consider the obtained 3D electrical resistivity models and the results of refraction seismic profiles. However, for a more detailed characterization of the vp and vs. values of lithotypes and the correlation with other observed geophysical parameters, a joint survey Seismic Refraction Tomography (SRT), Electrical Resistivity Tomography (ERT), and Induced Polarization Tomography (IPT) were carried out in coincident position [13]. Furthermore, a Transient Electromagnetic (TEM) survey was performed nearby.…”
Section: New Geophysical Surveysmentioning
confidence: 99%
“…Furthermore, the net of the actual cost of geophysical instrumentation, the relationship between the amount of data acquired and the economic evaluation of a geophysical survey make geophysical methodologies quite economical when compared to direct investigations. This approach had been often used in many studies regarding stratigraphic [1][2][3] and structural geology [4][5][6][7], the analysis of depositional sequences [8][9][10], archaeological [11][12][13] and civil engineering research [14][15][16]. In these studies, acquired geophysical data constrained by the information derived from direct investigation provide a fundamental tool for the integration and definition of subsurface models.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors demonstrated that reliable S-wave-velocity models can be obtained by inverting HVSR data with other stratigraphic and geophysical constraints [47,[49][50][51][52]. In particular, the uncertainty about the HVSR stratigraphic interpretation [53] can be addressed or at least limited using S-wave velocity models obtained by MASW as constraints [46,47,54].…”
Section: Introductionmentioning
confidence: 99%